Thermal conductivity of biobased insulation building materials measured by hot disk: Possibilities and recommendation. (November 2021) - Colinart, T.; Pajeot, M.; Vinceslas, T.; Hellouin De Menibus, A.; Lecompte, T.
Abstract: The Hot Disk transient plane source (TPS) method allows characterizing the thermal properties of various materials in a few minutes. Particularly, it is increasingly used for evaluating thermal conductivity of insulation building materials. However, the results of such measurement frequently differ from steady state measurements because of the significance of heat transfer into the Hot Disk sensor. Even if improvements have been proposed for specific cases, they cannot be generalized, especially for heterogeneous materials like biobased building insulation materials. The objective of this study is to evaluate all previously evaluated sources of errors when conducting a measurement with current capabilities of Hot Disk commercial device. Three types of material are tested: conventional isotropic materials (like XPS), compressible anisotropic materials (like wood fiber insulation) and heterogeneous anisotropic materials (like light-earth biobased concrete). The influence of setting parameters (volumetric heat capacity, temporal bound for estimation) is analyzed in light of repeatability and reproducibility errors. The suitability of hot disk method based on isotropic or anisotropic model to characterize non-transverse isotropic heterogeneous materials is discussed and compared with steady state measurements. Highlights: Thermal conductivity is measured by hot disk and guarded hot plate. Accurate results are obtained for isotropic building materials. Large uncertainties are observed for biobased building materials. Difficulties arise in evaluating anisotropic thermal behavior. Source of errors and influencing factors are evaluated.